Exploring HSP90 as a Biomarker for Marine Heatwaves in Pinctada maxima - Masanja, Fortunatus; Xu, Yang; He, Guixiang; Liang, Feilong; Liu, Xiaolong; Yang, Ke; Mkuye, Robert; Liang, Jian; Deng, Yuewen; Zhao, Liqiang (Frontiers in Marine Science, 2022)
Many species, particularly marine organisms, are becoming more vulnerable to marine heatwaves due to climate change. Marine species anticipate perishing during marine heatwaves, but there is a growing interest in learning why some can resist. Using Pinctada maxima as a model species, we were able to clone a full-length cDNA encoding HSP90 with a calculated open reading frame of 2031 residues of amino acids and a molecular mass estimate of 78.08 kD to understand better the effects of marine heatwaves on the HSP90 gene expression in pearl oysters. The sequence of amino acids in P. maxima HSP90 was quite similar to the HSP90 families of Pinctada fucata martensii. At 32°C and 36°C, the expression of PmHSP90 significantly expressed and reached its highest level at 6 h, implying that in pearl oysters’ response to acute marine heatwaves, HSP90 expression rapidly increased. Pearl oysters’ temperature response was relieved, as best demonstrated by the dramatically reduced expression levels of PmHSP90 in the frequently reoccurring marine heatwaves event. Using these findings, it is possible to predict acute and repeated marine heatwaves in pearl oysters using P. maxima HSP90 as a molecular biomarker.